MANDAT YURIDIS KEPOLISIAN DALAM PENANGGULANGAN KEJAHATAN SIBER PINJAMAN ONLINE ILEGAL DI KOTA SUKABUMI - Ruswanda, Rosliana Mutiara (Truth de Journal, 2025)
Cybercrime by illegal online loan desk collectors has become a serious problem, especially during the COVID-19 pandemic. This study analyzes the role of the Sukabumi City Resort Police in overcoming this problem. The method used is empirical descriptive research, emphasizing data collection and analysis to provide a detailed picture of the phenomenon and its law enforcement. The results show that the police are making preventive efforts, such as socialization through social media about the risks of illegal online loans, as well as repressive efforts through investigations to uncover the truth of the law. However, obstacles such as difficulties in tracking suspects due to the lack of digital forensic tools and the challenge of educating the public about the dangers of illegal online loans still exist. This research emphasizes the importance of increasing police capacity in technology and public education to overcome rampant cybercrime.